Edukasi Tentang Identifikasi Dan Pengendalian Hama Dan Penyakit Tanaman Kelapa Sawit Menggunakan Pestisida Nabati Di Desa Bangun Sari, Kecamatan Kampar Kiri Hilir, Kabupaten Kampar, Riau - Razita Hariani; Anna Dhora; Ellani Patitis; Nofrifaldi Nofrifaldi; Ardiansyah Hamid; Hanifah Khairiah; Sri Wahyuni (Politeknik Kampar, 2023)
Bangun Sari Village is a village in Kampar Kiri Hilir District. Judging from its geographical location, Bangun Sari Village has great potential for development as an oil palm plantation business. Behind its potential, there are disturbances that can reduce oil palm productivity, namely plant pest organisms. One of the caterpillars that eat oil palm leaves is the fire caterpillar (setora nitens). Fire caterpillar attacks are generally treated by using synthetic chemical pesticides. However, the use of synthetic chemical pesticides can have negative effects. The best solution to overcome this is to use vegetable pesticides. Many plants can be used as raw materials for vegetable pesticides, such as babadotan plants, lemongrass leaves, neem leaves and others. Based on surveys and interview results, the PKM team received information that the community had no knowledge of identifying and controlling plant pests and diseases. Therefore, pest and disease control must be right on target and carried out with good and correct procedures. Control measures are expected to increase palm oil production and productivity.